Small Firms’ Formalization : The Stick Treatment - De Giorgi, Giacomo; Ploenzke, Matthew; Rahman, Aminur (World Bank, Washington, DC, 2015)
Firm informality is pervasive throughout the developing world, Bangladesh being no exception. The informal status of many firms substantially reduces the tax basis and therefore impacts the provision of public goods. The literature on encouraging formalization has predominantly focused on reducing the direct costs of formalization and has found negligible impacts of such policies. This paper focuses on a stick intervention, which to the best of the knowledge of the authors is the first one in a developing country setting that deals with the most direct and dominant form of informality, i.e. registration with the tax authority with a direct link to the countrys potential revenue base and thus public goods provision. The paper implements an experiment in which firms are visited by tax representatives who deliver an official letter from the Bangladesh National Tax Authority stating that the firm is not registered and the consequential punishment if the firm fails to register. The paper finds that the intervention increases the rate of registration among treated firms, while firms located in the same market but not treated do not seem to respond significantly. The paper also finds that only larger revenue firms at baseline respond to the threat and register. These findings have at least two important policy implications: i. the enforcement angle, which could be an important tool to encourage formalization; and ii. targeting of government resources for formalization to the high-end informal firms. The effects are generally small in levels and this leaves open the question of why many firms still do not register.